Sistem Pendukung Keputusan Seleksi Tenaga Fasilitator Lapangan BSPS Menggunakan Metode Multi Factor Evaluation Process - Nur Oktavin Idris; A. Mulawati Mas Pratama; Muliati Badaruddin (STMIK Budi Darma, 2022)
Field facilitator workers shall guide the Self-Help Housing Stimulant Assistance Program (BSPS) recipients intensively, either in technical matters or the fund use realization process during construction terms. Guidance is given from planning, implementing a construction, and forming an assistance recipient community group that can construct decent housing independently. Accordingly, field facilitator workers are imperative to guide the BSPS recipient community. Public Works and Spatial Planning Office in Gorontalo is still selecting field facilitator workers manually, bringing on assessment errors in the selection process, e.g., selecting field facilitator workers that do not fulfill the requirement. Additionally, the sheer number of applicants overwhelms staff as they have to face off piling files of applicants. It brings about a longer selection process. As such, a systematic selection process based on the determined criteria is important. Later, it can act as a reference. It is called a decision-supporting system. Our decision-supporting system aims to help make decisions to select field facilitator workers guiding the BSPS recipient community using the Multi-Factor Evaluation Process (MFEP) method. The results point out Bambang achieved the highest final score of 87.675. Hence, MFEP in the supporting system is a recommended method to make decisions to select field facilitator workers guiding the BSPS recipient community in building decent housing.